1988
DOI: 10.1016/0020-7292(88)90080-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the glucose tolerance test in unselected pregnancy using 75 g glucose load

Abstract: A 75 g oral glucose tolerance test (OGTT) was performed in 618 unselected pregnant Chinese women between 24 and 28 weeks gestation. The glucose response at fasting, 1, 2 and 3 h were studied. At 2 h the glucose level at 2-standard deviation and 4-standard deviation above the mean came very close to the criteria of abnormality suggested by the World Health Organization (WHO): 8.3 mmol/l vs. 8.0 mmol/l for impaired glucose tolerance and 10.8 mmol/l vs. 11.0 mmol/l for gestational diabetes mellitus. The area unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Furthermore, work by Vallacott et al reveals that 50% of affected women believe their work efficiency to be significantly reduced [105]. …”
Section: Outcomementioning
confidence: 99%
“…Furthermore, work by Vallacott et al reveals that 50% of affected women believe their work efficiency to be significantly reduced [105]. …”
Section: Outcomementioning
confidence: 99%
“…It was proposed that the upper limits of normal for plasma glucose concentration 2 hours after a 75 g glucose load for the second and third trimesters were 7.5 and 9.6 mmol/L, respectively; these values were based on the rounded‐up 97.5 percentile measurements. Li et al 13 studied the glucose response of 75 g OGTT in 618 unselected pregnant Chinese women between 24 and 28 weeks gestation. It was found that the 2 hour glucose levels at 2‐standard deviation and 4‐standard deviation above the mean came very close to the criteria of abnormality suggested by WHO: 8.3 mmol/L and 10.8 mmol/L, respectively.…”
Section: Diagnosismentioning
confidence: 99%
“…Since 1986, the 2 teaching hospitals of the University of Hong Kong (Tsan Yuk Hospital and Kwong Wah Hospital) have adopted the 75 g OGTT and a modified WHO criteria (table 1) to diagnose gestational diabetes, following earlier studies conducted in the same unit to evaluate the 75 g OGTT (7,8).…”
Section: Initial Diagnosis Of Gestational Diabetesmentioning
confidence: 99%
“…A11 women with a random serum glucose value over 5.0 mmol/L more than 2 hours after meal, or over 5. 8 mmol/L within 2 hours of a meal were tested with a 75 g OGTT.…”
Section: Initial Diagnosis Of Gestational Diabetesmentioning
confidence: 99%